Assessment of Quality of Fetal Heart Views by 3D/4D Ultrasonography Using Spatio‐Temporal Image Correlation in the Second and Third Trimesters of Pregnancy. Issue 6 (18th September 2014) - Rocha, Luciane Alves; Rolo, Liliam Cristine; Barros, Fernanda Silveira Bello; Nardozza, Luciano Marcondes Machado; Moron, Antonio Fernandes; Araujo Júnior, Edward
<x xml:space="preserve">Abstract</x> Objective To assess the quality of fetal heart views by three‐dimensional/four‐dimensional (3D/4D) ultrasonography using spatio‐temporal image correlation (STIC) in the second and third trimester of pregnancy. Methods This prospective and cross‐sectional study was conducted at a single referral service for the screening of congenital heart diseases (CHDs), with pregnant women at 20–30 weeks' gestation with a normal fetal heart. 3D/4D STIC were obtained from the fetal heart screening in the following views: four‐chamber (4C), left and right ventricular outflow tracts (LVOT and RVOT), 3 vessels and trachea (3VT), aortic arch (AA), and ductal arch (DA). We categorized the images as satisfactory or unsatisfactory and performed McNemar's test to evaluate the differences between the two‐dimensional (2D) echocardiography and 3D/4D STIC techniques. The inter‐observer concordance was obtained by kappa coefficient. Results The rate of satisfactory fetal heart views using 3D/4D STIC was 54% by using 4 planes (4C, RVOT, LVOT, and 3VT) and 14% by using 6 planes (4C, RVOT, LVOT, 3VT, AA, and DA). In contrast, 100% of the 2D echocardiography images were satisfactory (McNemar's test, P < 0.001). We observed moderate inter‐observer concordance to both 4‐ and 6 planes (κ = 0.56 and 0.43, respectively). Conclusion The quality of the main fetal heart views by 3D/4D STIC still present some limitations compared with the 2D echocardiography.